Factors influencing the practice of Smoking Cessation Assessment and Management among Primary Care Doctors (SCAAM-DOC) in three districts of Malaysia - Jee, Beatrice Ngee Ling; Cheong, Ai Theng; Abdul Manap, Abdul Hadi (Public Library of Science (PLOS), 2022)
Background Smoking prevalence remains high in Malaysia. Primary care doctors have a good opportunity to motivate the smokers to quit smoking in view of the accessibility of primary healthcare clinics to the public. The objective of this study was to determine the practice of smoking cessation management among primary care doctors and its associated factors. Methods A cross-sectional online survey was carried out among 383 medical officers and interns in all government primary healthcare clinics in the district of Petaling, Klang and Hulu Langat from June to August 2020. All doctors were involved in the care of patients for smoking cessation. The knowledge, attitude and practice of smoking cessation management were assessed using a 17-items validated questionnaire which covered the components of 5As (Ask, advise, assess, assist, arrange) and 5Rs (Relevance, risk, reward, roadblocks, repetition). The management of pre-contemplation phase included the components of ask, advise, assess and 5Rs. The management of the contemplation phase included the components of assist and arrange. Result The majority of the respondents had poor score of knowledge (62.4%); attitude (58%) and practice (pre-contemplation management:50.9%; contemplation management:75.7%). Using multivariate logistic regression analysis, the significant factors associated with the poor practice of smoking cessation management in the pre-contemplation phase were poor (OR = 2.14, 95% CI 1.11–4.12, p <0.01) or moderate knowledge (OR = 2.50, 95% CI 1.19–5.26, p<0.01), poor attitude (OR = 2.16, 95% CI 1.39–3.37, p<0.01), lacks smoking cessation banners, brochures and leaflets in the clinic (OR = 2.01, 95%CI 1.26–3.19, p<0.01) and lack of nicotine replacement medications (OR = 2.27. 95%CI 1.27–4.06, p<0.01). No significant factors were shown associated with the practice of the contemplation phase. Conclusion The majority of primary care doctors had poor knowledge, attitude and practice of smoking cessation management. Factors that had increased the odds of the poor practice of smoking management at the pre-contemplation phase were poor knowledge, poor attitude, and insufficient organizational support for health promotion materials and nicotine replacement medication.